(untitled) (Ameghiniana, 2013)
On the basis of the study of the specific diversity (Shannon-Weaver ) and similarity (Sorensen) among 12 samples retrieved from DSDP Site 173 (northem Pacífíc ), which ranga from the upper Oligocene to the Pleistocene, it is concluded that: a) highest diversity occurred during the middle Miocene, and b) during this period there have not been conspícuous or sharp faunistic changes, they occurrecl more or less gradually, with somewhat more noticeable "breaks" at the Oligocene-Miocene and Miocene-Pliocene boundaries. Upper Oligocene and Pliocene assernblages are very similar; over half of the species are common to both systems. Moreover, it is suggested that more extensive coJlections than those studíed will show that the percentage of common taxa is even higher than our results indicate.